Iodine and inorganic iodides : human health aspects - Risher, J; Keith, L. Samuel (World Health Organization, 2009)
Iodine is a naturally occurring element and inorganic iodines found in the ocean accumulate in fish, shellfish and seaweed. Industrially iodine is used in many applications including the manufacture of inks, dyes, photographic agents and in water-purification. In the health-care industry, iodine is widely used as a disinfectant/biocide and in the production of soaps, bandages, and medicines. Iodine is also included as a salt in some countries to provide dietary supplementation. This Concise International Chemical Assessment Document (CICAD) evaluates the scientific literature on the health aspects of iodine and inorganic iodides. Its focus is on the health effects from environmental exposures beyond those associated with the diet and nutritional supplementation. Radioactive iodine isotopes are regarded as outside the scope of the document.
Concise international chemical assessment document, ISSN 1020-6167 72
Keywords: Iodine; jodidy; Risk Assessment; Iodides; hodnocení rizik; maximální přípustná koncentrace; Environmental Exposure; Maximum Allowable Concentration; jod; Iodine Compounds; environmentální vědy; sloučeniny jodu; vystavení vlivu životního prostředí; toxikologie